The influences of the Big Five personality traits on academic achievements: Chain mediating effect based on major identity and self-efficacy - Wang, Hui; Liu, Yuxia; Wang, Zhanying; Wang, Ting (Frontiers in Psychology, 2023)
This study mainly verified the influences of personality traits on students’ academic achievements and assessed the mediating effects of major identity and self-efficacy, under the classical model of chain mediating effects, with the data of business major students. The results show that both extraversion and conscientiousness have positive total effect on students’ academic achievements, and they are mainly realized through the chain mediating effects of self-efficacy and major identity to self-efficacy, and are mainly based on self-efficacy mediating effect, which is more obvious in the dimension of behavioral efficacy. Openness also affects academic achievement through a self-efficacy mediating effect and major identity to self-efficacy chain mediating effect, but the degree of influence is weak, and the total effect is not significant; the overall effect of agreeableness personality on academic achievement is negative, and it is mainly reflected through direct effect. This finding suggests that academic achievement does not reflect students’ team ability and performance.